The Relationship Between Pregnant Women’s Knowledge of Anemia and Adherence to Iron Tablet Consumption at Bener Kelipah Community Health Center, Bener Meriah Regency, 2025 - Sembiring, Dessy Ratna Sari; Yun, Deby Chyntia (Fakultas Kedokteran, Universitas Papua, 2025)
Anemia during pregnancy is a health problem that has serious impacts on both the mother and fetus, such as increasing the risk of preterm delivery, low birth weight, and delivery complications. One preventive measure is the provision of iron tablets; however, pregnant women’s adherence to consuming them is often influenced by their knowledge of anemia. This study aimed to determine the relationship between pregnant women’s knowledge of anemia and adherence to iron tablet consumption at Bener Kelipah Community Health Center, Bener Kelipah Subdistrict, Bener Meriah Regency, in 2025. This research employed an analytical observational design with a cross-sectional approach involving 32 pregnant women in their second and third trimesters, selected using accidental sampling. Data were collected using a structured questionnaire and analyzed univariately and bivariately using the chi-square test. The results showed that 69.7% of respondents had low knowledge and did not regularly consume iron tablets, while 31.3% had sufficient knowledge but still did not consume them regularly. The chi-square test revealed a significant relationship between pregnant women’s knowledge of anemia and adherence to iron tablet consumption (p = 0.001; p < 0.05). It is concluded that pregnant women’s knowledge influences adherence to iron tablet consumption; therefore, comprehensive nutritional and health education from healthcare providers is essential to improve adherence and prevent anemia during pregnancy.